2011
DOI: 10.1002/smi.1317
|View full text |Cite
|
Sign up to set email alerts
|

Irritant‐drinking behaviour can be modified by gravity‐stress loaded in developing but not in adult rats

Abstract: It is generally accepted that taste and taste‐related trigeminal chemical sensation bring up emotions that are essential for animal living and for a good quality of life, and that stress may modify sensory systems related to emotionality. The purpose of this study was to clarify (1) the effects of stress on taste and trigeminal irritant sensations, (2) effects of stress at a developing stage on these sensations. Male Wistar albino rats received 1G, 2G or 3G stimulation. Hyper‐gravity was applied with a centrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Therefore, it is presumed that stress-modified trigeminal pain sensation may strongly depend on sex. A similar interaction has been reported in relation to taste sensation during food intake [40].…”
Section: Strong (20g) Gravity-stresssupporting
confidence: 84%
“…Therefore, it is presumed that stress-modified trigeminal pain sensation may strongly depend on sex. A similar interaction has been reported in relation to taste sensation during food intake [40].…”
Section: Strong (20g) Gravity-stresssupporting
confidence: 84%
“…The animals were moved in pairs from the colony room to the centrifuge room and loaded into the centrifuge. A centrifugal apparatus (H26-F, Kokusan, Tokyo, Japan) was used, as described elsewhere (10). The arm length of the centrifuge was 15 cm, and to produce hyperG, the speed of rotation was set to 108 rpm (resulting in an acceleration vector of 2.2 G).…”
Section: Methodsmentioning
confidence: 99%
“…However, careful consideration on possible side-effects of centrifugation on all bodily functions and systems should be carried out before it can be used in a regular basis. Previous animal studies have shown general effects of hypergravity in the body, such as changes in body weight and gustatory sensation in rats (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…3G stress was loaded by a centrifugal apparatus (H26-F, Kokusan, Tokyo, Japan) every day at 10:00 AM for 10 min during 30 days, as described elsewhere [20]. During gravity-loading, rats were placed in the mesh case of the centrifuge with a head-central orientation.…”
Section: Stress Conditioningmentioning
confidence: 99%
“…Nevertheless, the relationship between stress and somatostatin is still controversial. Further, sex differences are usually observed in stress responses, including changes in digestive function and feeding behavior [20][21][22].…”
Section: Introductionmentioning
confidence: 99%